A case report of cardiac amyloidosis presenting with chronic pericardial effusion and conduction block. Issue 4 (24th September 2019) - John, Kevin John; Mishra, Ajay Kumar; Iyyadurai, Ramya
Abstract: Background: Amyloidosis is caused by the deposition of abnormal proteins in the extracellular space of various organs. The clinical features of amyloidosis depend on the type of amyloid protein and the organ system involved. Case summary: A 51-year-old woman developed complete heart block which warranted a permanent pacemaker insertion. She was referred for evaluation of chronic pericardial effusion. The patient had stable vital signs and muffled heart sounds on examination of the cardiovascular system. Her chest X-ray film showed a permanent pacemaker in situ, and echocardiogram showed a chronic pericardial effusion without features of tamponade. On further evaluation, she was found to have an M band on serum electrophoresis, elevated free light chain ratio and amyloid deposits in bone marrow biopsy. Technetium pyrophosphate (Tc-PYP) scintigraphy was consistent with cardiac amyloidosis. Discussion: Cardiac amyloidosis can have diverse clinical presentations. Chronic pericardial effusion and conduction block can be a rare presentation of cardiac amyloidosis and needs to be considered while evaluating the same. Cardiac magnetic resonance imaging and Tc-PYP imaging can be used in establishing the diagnosis of cardiac amyloidosis, if endomyocardial biopsy is not feasible.